The Supplementation of Cinnamaldehyde in Semen Extender to Improve the Post‐Thaw Sperm Quality of Kajli Ram Semen - Saima Qadeer; Asma Ashraf; Naila Perveen; Muhammad Asad; Asma Ul Husna; Asima Azam; Muhammad Umer Farooq; Abdullah S. Alhomida; Haseeb A. Khan (Veterinary Medicine and Science)
ABSTRACT Cinnamaldehyde, a component of cinnamon bark extract, acts as a potential antioxidant by enhancing the activities of catalase, superoxide dismutase and glutathione peroxidase in various cell and animal models. This study aimed to evaluate the protective effects of cinnamaldehyde on the quality of Kajli ram sperm at 4°C and after freezing. Semen samples were obtained from 12 Kajli rams through an artificial vagina maintained at 42°C. Each ejaculate was divided into five aliquots and extended in a tris‐citric acid extender with different concentrations of cinnamaldehyde (0%, 0.5%, 1.0%, 2.5% and 5.0%). Post‐thaw semen quality was assessed. These results showed that the extender containing 0.5% cinnamaldehyde exhibited significant protective effects (p < 0.05) on post‐thaw sperm plasma membrane and sperm viability compared to the control and other experimental groups. In conclusion, supplementing the extender with 0.5% cinnamaldehyde effectively preserved the quality of post‐thawed sperm from Kajli rams.